Endoscopic management of postcholecystectomy complications at a Nigerian tertiary health facility - Olusegun Isaac Alatise; Patrick Ayodeji Akinyemi; Afolabi Olumuyiwa Owojuyigbe; Titilayo Adenike Ojumu; Adeleye Dorcas Omisore; Adewale Aderounmu; Aburime Ekinadese; Akwi Wasi Asombang (BMC Gastroenterology)
Abstract Background Cholecystectomy and common bile duct exploration for biliary stone disease are common hepatobiliary surgeries performed by general surgeons in Nigeria. These procedures can be complicated by injury to the biliary tree or retained stones, requiring repeat surgical intervention. This study presents the experience of using endoscopic retrograde cholangiopancreatography (ERCP) in the management of hepatobiliary surgery complications at the academic referral center of Obafemi Awolowo University Teaching Hospital (OAUTHC) Ile-Ife, Nigeria. Methods All patients with postcholecystectomy complications referred to the endoscopy unit at OAUTHC from March 2018 to April 2023 were enrolled. Preoperative imaging included a combination of abdominal ultrasound, CT, MRI, magnetic resonance cholangiopancreatography (MRCP), and T-tube cholangiogram. All ERCP procedures were performed under general anesthesia. Results Seventy-two ERCP procedures were performed on 45 patients referred for postcholecystectomy complications. The most common mode of presentation was ascending cholangitis [16 (35.6%)], followed by persistent biliary fistula [12 (26.7%)]. The overall median duration of symptoms after cholecystectomy was 20 weeks, with a range of 1-162 weeks. The most common postcholecystectomy complication observed was retained stone [16 (35.6%)]. Other postcholecystectomy complications included bile leakage, bile stricture, bile leakage with stricture, and persistent bile leakage from the T-tube in 12 (26.7%), 11 (24.4%), 4 (8.9%), and 2 (4.4%) patients, respectively. Ampullary cannulation during ERCP was successful in all patients (45, 100%). Patients with complete biliary stricture (10/12) required hepaticojejunostomy. Conclusion Endoscopic management of postcholecystectomy complications was found to be safe and reduce the number of needless surgeries to which such patients are exposed. We recommended prompt referral of such patients for ERCP.